ENHANCING BLOOD SUGAR CONTROL IN TYPE II DIABETES MELLITUS THROUGH NON-PHARMACOLOGICAL FOOT EXERCISE THERAPY: A QUALITATIVE CASE STUDY - Putra, Kusuma Wijaya Ridi; Anam, Akhmad Khoirul; Ana, Karisma Dwi (Library Unit collaborates with the Institute for Research and Community Service, College of Health Sciences Husada Jombang, 2025)
Background: Type II Diabetes Mellitus (DM) is a chronic metabolic disorder often accompanied by blood glucose instability, increasing the risk of long-term complications. Non-pharmacological interventions such as foot exercise therapy offer a complementary approach to blood sugar control. Objectives: The study was to evaluate the effectiveness of non-pharmacological foot exercise therapy in enhancing blood sugar control in Type II DM patients. Design: This qualitative case study involved two patients with Type II DM who experienced unstable blood glucose levels at the Sedap Malam Room, RSI Nashrul Ummah Lamongan. Nursing care included implementing diabetic foot exercise therapy performed once daily for three consecutive days. Blood glucose levels were measured before and after the intervention using a glucometer. Data were analyzed descriptively. Results: Both patients demonstrated a reduction in blood glucose levels. Patient 1's blood glucose decreased from 244 mg/dl to 181 mg/dl, while Patient 2's dropped from 265 mg/dl to 160 mg/dl. Additional outcomes included reduced fatigue and improved self-management awareness. Conclusion: Non-pharmacological foot exercise therapy effectively lowered blood glucose levels in Type II DM patients. This therapy can serve as a supportive nursing intervention to enhance glycemic control, minimize complications, and improve patient quality of life.